Virtual reality, augmented reality and tourism experience - Loureiro, S. M. C. (The Routledge handbook of tourism experience management and marketing, 2020)
This chapter intends to give an overview of tourist experience in the real and virtual worlds (virtual and augmented reality) and how tourists are dealing with these two worlds. To achieve such a goal, the chapter examines existing definitions and conceptualizations of experience (and related constructs), virtual reality (VR) and augmented reality (AR) and delivers a historical perspective of real and virtual experiences within tourism. A comprehensive literature review makes it possible to methodologically capture the concepts of the topic and organize the structure of the chapter giving (i) different experience definitions, (ii) definitions of VR and AR, (iii) the root of experience in tourism (e.g., service quality, satisfaction, relationship marketing, tourist focus, tourist engagement, co-creation), and (iv) the tourist experience journey (stages of tourism experience and its relationship with VR and AR). The chapter is of interest to both academics and practitioners, since it identifies concepts of tourism experience, aggregating the real and virtual worlds, and at the same time gives a view of tourist experience management. Finally, the chapter points out critical areas for future research.